2022
DOI: 10.1002/pat.5736
|View full text |Cite
|
Sign up to set email alerts
|

Amide polymers based on N‐phenyl‐p‐phenylenediamine with α‐olefins‐co‐maleic anhydride as multifunctional additives for lubricant application

Abstract: The high temperature and harsh oxidizing conditions in engine sump results in sludge and varnish deposits in the engine, due to which wear debris and corrosion developed in the internal parts of the engine. This is also responsible for the increased oil viscosity. To address these problems, four polymeric multifunctional amides of N‐phenyl‐p‐phenylenediamine were synthesized from copolymer intermediates poly(α‐olefins‐co‐maleic anhydride) having C‐12, C‐14, C‐16, and C‐18 chain length. This article describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This arrangement establishes a hydrocarbon surface with low shear strength on metal surfaces. At present, the developed OFMs incorporate various polar functional groups, such as carboxyl [20][21][22], alcohol [23][24][25], amine [26,27], amide [5,[28][29][30], and ester [31] functionalities. Biresaw [31] synthesized seven lipoic acid esters using various alcohols, and the study showed that the performance of thioic acid multifunctional additives in base oils is related to its structure.…”
Section: Introductionmentioning
confidence: 99%
“…This arrangement establishes a hydrocarbon surface with low shear strength on metal surfaces. At present, the developed OFMs incorporate various polar functional groups, such as carboxyl [20][21][22], alcohol [23][24][25], amine [26,27], amide [5,[28][29][30], and ester [31] functionalities. Biresaw [31] synthesized seven lipoic acid esters using various alcohols, and the study showed that the performance of thioic acid multifunctional additives in base oils is related to its structure.…”
Section: Introductionmentioning
confidence: 99%
“…into a high-strength polymer matrix (PEEK, PPS, PI, etc. ), ensuring the formation of a high-wear-resistance transfer film on the counterpart, which preserves the strain-hardened properties of the neat polymer [6][7][8][9][10][11][12][13][14][15][16]. Among the various non-metallic and metallic solid lubricant fillers applied in thermoplastic composites, previous works have discussed the positive effects of incorporating a mass content of carbon-based materials not exceeding 10 wt.% to Polyamide 66 (PA66) or ultrahigh-molecular-weight polyethylene (UHMWPE) matrixes on the tribological properties of the composites [6,8].…”
Section: Introductionmentioning
confidence: 99%